Delayed granulomatous reactions to facial cosmetic injections of polymethylmethacrylate microspheres and liquid injectable silicone: A case series. (2nd April 2016) - Friedmann, Daniel P.; Kurian, Anil; Fitzpatrick, Richard E.
Abstract : Polymethylmethacrylate microsphere (PMMA) and liquid injectable silicone (LIS) fillers are non-biodegradable, synthetic polymers utilized for long-term soft-tissue augmentation. Delayed granulomatous reactions to permanent fillers are a rare yet significant event that can occur months to years post procedure and are often refractory to treatment and associated with significant cosmetic morbidity. We report a case series of 4 patients who developed granulomatous reactions to PMMA or LIS, 15 months to 5 years post injection. The etiology of granulomatous reactions to permanent fillers is still poorly understood, with foreign-body reactions and/or biofilms purported to play a role. Real-time biochemical analysis with polymerase chain reaction should be performed when the index of suspicion for the presence of a biofilm is high.